Motivating Process Compliance Through Individual Electronic Monitoring: An Empirical Examination of Hand Hygiene in Healthcare - Staats, Bradley R.; Dai, Hengchen; Hofmann, David; Milkman, Katherine L. (Management Science, 2017)
The design and use of standard processes are foundational recommendations in many operations practices. Yet, given the demonstrated performance benefits of standardized processes, it is surprising that they are often not followed consistently. One way to ensure greater compliance is by electronically monitoring the activities of individuals, although such aggressive monitoring poses the risk of inducing backlash. In the setting of hand hygiene in healthcare, a context where compliance with standard processes is frequently less than 50% and where this lack of compliance can result in negative consequences, we investigated the effectiveness of electronic monitoring. We did so using a unique, radio frequency identification (RFID)-based system deployed in 71 hospital units. We found that electronically monitoring individual compliance resulted in a large, positive increase in compliance. We also found that there was substantial variability in the effect across units and that units with higher levels of preactivation compliance experienced increased benefits from monitoring relative to units with lower levels of prepreactivation compliance. By observing compliance rates over three and a half years, we investigated the persistent effects of individual monitoring and found that compliance rates initially increased before they gradually declined. Additionally, in multiple units, individual monitoring was discontinued, allowing for an investigation of the impact of removing the intervention on compliance. Surprisingly, we found that, after removal, compliance rates declined to below prepreactivation levels. Our findings suggest that, although individual electronic monitoring can dramatically improve process compliance, it requires sustained managerial commitment. This paper was accepted by Serguei Netessine, operations management.